Conjunctival and corneal reactions in rabbits following short- and repeated exposure to preservative-free tafluprost, commercially available latanoprost and 0.02% benzalkonium chloride - Liang, H (BMJ Publishing Group, 2008)
AIM: To compare the conjunctival and corneal reactions of commercially available solution of latanoprost (Xalatan) and preservative-free (PF) tafluprost in rabbits. METHODS: The rabbits received 50 μl of phosphate-buffered saline (PBS), PF-tafluprost 0.0015%, latanoprost 0.005% or benzalkonium chloride (BAK) 0.02%; all solutions were applied at 5 min intervals for a total of 15 times. The ocular surface toxicity was investigated using slit-lamp biomicroscopy examination, flow cytometry (FCM) and on imprints for CD45 and tumour necrosis factor-receptor 1 (TNFR1) conjunctival impression cytology (CIC) and corneal in vivo confocal microscopy (IVCM). Standard immunohistology also assessed inflammatory/apoptotic cells. RESULTS: Clinical observation and IVCM images showed the highest ocular surface toxicity with latanoprost and BAK, while PF-tafluprost and PBS eyes presented almost normal corneoconjunctival aspects. FCM showed a higher expression of CD45+ and TNFR1+ in latanoprost- or BAK-instilled groups, compared with PF-tafluprost and PBS groups. Latanoprost induced fewer positive cells for inflammatory marker expressions in CIC specimens compared with BAK-alone, both of which were higher than with PF-tafluprost or PBS. Immunohistology showed the same tendency of toxic ranking. CONCLUSION: The authors confirm that rabbit corneoconjunctival surfaces presented a better tolerance when treated with PF-tafluprost compared with commercially available latanoprost or BAK solution.